Exploratory Survey of Teachers’ and Students’ Perceptions of Etnomatematics in Traditional Games - Julius Martunas Sihite; Neli Permatasari; Yudha Ningsih; Hilda Mardiyana; Huri Suhendri; Arfatin Nurrahmah (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2025)
Ethnomathematics has emerged as one such strategy, offering an approach that connects mathematical concepts with cultural practices, traditions, and local wisdom. This study investigates teachers’ and students’ perceptions of using the traditional games engklek and congklak in mathematics learning at MTsN 2 Kota Tangerang. The research employed a qualitative exploratory survey involving five mathematics teachers and sixty students selected through purposive sampling. Data were collected using open-ended questionnaires, semi-structured interviews, classroom observations, and documentation, and analyzed through thematic analysis. The results show that both teachers and students perceive traditional games as effective tools for supporting mathematical understanding. Engklek helps students visualize geometric concepts such as lines, angles, and shapes, while congklak strengthens number sense, arithmetic operations, and strategic thinking. Students reported higher motivation, enjoyment, and clarity during game-based learning activities. Teachers also noted that traditional games make abstract concepts easier to understand and more connected to students’ cultural experiences. Despite these benefits, challenges were identified, including limited structured teaching materials and the need for teacher training. Overall, the integration of ethnomathematics through traditional games aligns with the goals of the Merdeka Curriculum and offers a practical approach to making mathematics more engaging and culturally relevant.